(untitled) (Research, Society and Development, 2024)
Nile tilapia, due to its regenerative properties and biocompatibility, is emerging as a promising alternative in veterinary medicine. The use of tilapia has received attention due to its composition rich in collagen, a component known for its ability to guide and define most tissues. This study aims to present a case report with an innovative approach to the treatment of mandibular fractures in felines, using Nile tilapia skin as a biological dressing associated with the technique of fixation of the mental symphysis by cerclage and the use of an advancement flap in the reconstruction of the mandible. The results demonstrated efficient healing and reduction of postoperative complications, evidencing the therapeutic potential of this approach in veterinary medicine. The use of tilapia skin proved to be a crucial element in the treatment, providing satisfactory results and accelerating the animal’s recovery. This case reinforces the importance of searching for innovative and effective approaches in the treatment of injuries in animals, contributing to the continuous improvement of veterinary care.